Development of a single honeypot system interface - Ahmad, Siti Rohaidah; Ahmad, Arniyati; Abd Hamid, Nazatul Naquiah Ahba; Ab Rajab, Mohd Sharif; Awang, Nor Fatimah; Wook, Muslihah (2011)
Networking is crucial to any organization which interconnecting systems all around the globe. However, networking is exposed to the increase of threats that have been detected which reducing the organization’s security level.Perpetrators of cybercrime will take this advantage to exploit other systems in their network.To enhance the security level of networking, Honeypot technology has been created to detect the unauthorized use of network.This paper focuses on development of batch files that execute a normal computer as a Honeypot. The main goal of this system is to capture information on every network attacks.Technically, this paper will guide user in Honeypot configuration process.